Effect of Dietary Incorporation of Lemongrass (Cymbopogon citratus) Essential Oil on the Nutrient Metabolism, Carcass Characteristics and Gut Microbes of Broilers - Amit,; Joshi, Monika; Meel, Mahendar Singh; Saraswat, Abhishek; Meel, Mamta; Yadav, Balram; Garg, Shruti (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from July-September, 2024 at the Poultry unit of the College of Veterinary and Animal Science, Navania, Vallabhnagar, Udaipur (Rajasthan), India to study the effect of dietary inclusion of the herbal feed additive lemongrass (Cymbopogon citratus) essential oil on nutrient metabolism, carcass characteristics, and gut microbes as an alternative to antibiotic feed additives. A six-week experimental trial was conducted on ninety-six day-old (VENCOBB-400) broiler chicks, which were divided into four treatment groups. The chicks were fed a broiler basal diet in the T1 group, a broiler basal diet with 3 ml kg-1 lemongrass essential oil in the T2 group, a broiler basal diet with 3.5 ml kg-1 lemongrass essential oil in the T3 group, and a broiler basal diet with 4 ml kg-1 lemongrass essential oil in the T4 group. During the last week of the six-week trial period, two birds per replicate under each treatment were randomly selected and shifted to metabolic cages to conduct a nutrient metabolism trial. On the 42nd day, birds were sacrificed for carcass study and gut microbial assay. The results showed substantial improvements (p<0.05) in the metabolism of dry matter, crude protein, nitrogen-free extract, and crude fiber, while the metabolism of ether extract and total ash showed non-significant changes (p>0.05). The percentage of eviscerated weight increased significantly (p<0.05), while the percentage of dressing weight and giblets weight varied non-significantly (p>0.05). Additionally, there was a highly significant (p<0.01) reduction in E. coli and total viable count.